Impact of image fusion and attenuation correction by SPECT-CT on the scintigraphic detection of parathyroid adenomas - Ruf, J.; Seehofer, D.; Denecke, T.; Stelter, L.; Rayes, N.; Felix, R.; Amthauer, H. (Nuklearmedizin - NuclearMedicine, 2007)
Aim: In addition to planar parathyroid scintigraphy, SPECT and image fusion with CT/MR improve adenoma detection in primary hyperparathyroidism (pHPT). This study evaluated the use of a hybrid SPECT-CT device concerning image fusion and attenuation correction (AC). Patients, methods: The data of 26 patients with pHPT, preoperatively examined by 99mTc-sestamibi dual-phase scintigraphy plus SPECT-CT (low-dose CT), was retrospectively evaluated by two observers in a consensus reading. The images of planar scintigraphy, non-attenuation corrected SPECT (SPECTNAC), attenuation corrected SPECT (SPECTAC) and SPECTAC-CT were interpreted and compared to the results of surgery. The effect of AC on focus intensity was semiquantified by determination of the tumor-to-background (TB) ratio for SPECTAC and SPECTNAC. Finally, the TBAC/TBNAC-ratio was calculated for each focus and correlated to the distance of a focus from the body surface. Results: 20/26 (77%) patients were positive in planar scintigraphy. One focus was detected by SPECT only. AC of SPECT-data increased image contrast but had no impact on the detection rate. Additional SPECTAC-CT image fusion facilitated the localization of three mediastinal foci. In the semiquantitative analysis an increase in TB after AC was observed, although there was no strong correlation between depth of the focus (16-60 mm) and the TBAC/TBNAC-ratio (r = 0.213, p = 0.353). Conclusion: The detection rate of planar scintigraphy is only slightly improved by SPECT imaging. Due to the low spatial resolution of the CT component, the benefit of image fusion is limited to mediastinal foci. However, as TB and image contrast is measurably improved after AC there is a potential to improve the sensitivity of parathyroid SPECT.
Keywords: SPECT; attenuation correction; parathyroid scintigraphy; primary hyperparathyroidism; image fusion